Digital Age Issues: The Untheorized Revolution of Hypertext - Camodeca, Paulo Daniel (Tropelías: Review of Literary Theory and Comparative Literature, 2019)
This article is aimed to revise and briefly synthetize some of the technical revolutions which dazzled and overwhelmed philosophers and theorists throughout the western history in order to measure the size of the digital revolution in our days. Hypertext is a core concept to this purpose and its definitions, usages and some theoretical streams are explored as well as its current situation. Some of the streams which tried to define hypertextuality as a way of transtextuality without relating to electronic devices are also appointed so that some of the shortcomings affecting this concept come to light. Finally, some of the narrative structural problems regarding technological issues are also shown.
Keywords: Digital Revolution; Technique; Hypertext; Hypertextuality; linear and non-linear narratives; Hypermedia; Hyperfiction